The growth and characterization of Chromium-based p-type transparent conducting oxides - Farrell, Leo (Trinity College (Dublin, Ireland). School of Physics, 2016)
Two Cr-related materials Cr203 and CuCr02 are investigated as p-type transparent conducting oxides. They both have Cr in its electron configuration, a feature that is responsible for the p-type conductivity. Epitaxial Cr203 was grown by electron-beam evaporation in a molecular beam epitaxy system on c-plane sapphire. The growth parameters are discussed with an examination of the structural properties. The influence of Mg dopants and the oxygen partial pressure were investigated by thermoelectric and electrical measurements. The conduction mechanism is analysed using the small polaron hopping model, and hopping activation energies have been determined, which vary with doping concentration in the range of 210-300±5meV. Films with better conductivity were obtained by post-annealing. The effect of post-annealing is discussed in terms of a crystallographic reordering of the Mg dopant
Keywords: Physics, Ph.D.; PhD Trinity College Dublin, 2016